LIVING HADITH IN JAVANESE MUSLIM SOCIETY: Studi of Sesaji Rewanda Tradition in Semarang - Munsarif, Alyatal Husn; Zakiyah, Qonita; Musyafiq, Ahmad; Rochmawati, Nikmah; Ilhami, Muhammad Sodik (RIWAYAH, 2025)
The Sesaji Rewanda tradition at Kreo Cave, Semarang, serves as a tangible manifestation of Living Hadith, wherein the prophetic value of ihsan is actualized within the cultural framework of Javanese Muslim society. This study examines the intersection between local tradition and Islamic textuality, focusing on the ritual of Gunungan Sego Kethek, the collective feeding of wild monkeys, as an expression of compassion toward living beings. Employing a qualitative methodology, this research integrates a Living Hadith approach by synthesizing textual analysis of relevant prophetic traditions and classical commentaries (sharh) by Ibn Ḥajar al-ʿAsqalānī, Imam al-Nawawī, and Ibn Rajab al-Ḥanbalī, complemented by ethnographic observations of the ritual praxis. The findings indicate that the Sesaji Rewanda tradition represents the principle of ihsan ila al-ḥayawan (kindness toward animals), elevating cultural practice into a form of worship (‘ibadah) provided it remains within the boundaries of monotheistic (tawhid) principles. Furthermore, this study highlights how the tradition creates a harmonious synergy between religion, local culture, and ecological preservation. By contextualizing prophetic values into communal life, Sesaji Rewanda functions as a medium for transformative da’wah and socio-ecological ethics, proving that the Sunnah can be dynamically preserved through intimate local wisdom and inclusive cultural expressions. [Tradisi Sesaji Rewanda di Gua Kreo, Semarang, merupakan manifestasi nyata dari Living Hadis, di mana nilai profetik ihsan diaktualisasikan dalam kerangka budaya masyarakat Muslim Jawa. Penelitian ini mengkaji titik temu antara tradisi lokal dan tekstualitas Islam, dengan fokus pada ritual Gunungan Sego Kethek, di mana praktiknya memberi makan kepada monyet liar secara kolektif, sebagai bentuk ekspresi kasih sayang terhadap sesama makhluk hidup. Menggunakan metodologi kualitatif, penelitian ini mengintegrasikan pendekatan living hadis dengan menyintesis analisis tekstual terhadap hadis-hadis terkait serta syarah klasik dari Ibn Ḥajar al-ʿAsqalānī, Imam al-Nawawī, dan Ibn Rajab al-Ḥanbalī, yang dipadukan dengan observasi etnografis atas praksis ritual tersebut. Temuan penelitian menunjukkan bahwa tradisi Sesaji Rewanda merepresentasikan prinsip ihsan ila al-ḥayawan (berbuat baik kepada hewan), yang mengangkat praktik budaya menjadi sebuah nilai ibadah sejauh tetap terjaga dalam batasan prinsip tauhid. Lebih lanjut, studi ini menyoroti bagaimana tradisi tersebut menciptakan sinergi yang harmonis antara agama, budaya lokal, dan pelestarian ekologis. Dengan mengontekstualisasikan nilai-nilai kenabian ke dalam kehidupan komunal, Sesaji Rewanda berfungsi sebagai medium transformasi dakwah dan etika sosio-ekologis, yang membuktikan bahwa sunnah dapat dipelihara secara dinamis melalui kearifan lokal yang intim dan ekspresi budaya yang inklusif.]